KAJIAN CRC32 UNTUK MENDETEKSI PERUBAHAN ISI FILE DOCUMENT - Indra M. Sarkis (Universitas Methodist Indonesia, 2015)
Cyclic redundancy check 32 Bit or known by CRC32 is a technique used in data communication to check thedamage information sent or received between the sender and receiver are working at the data link layer on layer of the Open Systems Interconnection (OSI) by comparing the checksum value frames are sent to the framereceived during transmission takes place. CRC32 techniques applied attempted to detect changes in a file that may occur due to human vandal through virus attack. In this study CRC 32 is applied with the same technique, namely by comparing the checksum of a file obtained from the registry system with the hash function of the value of the checksum file to be compared. From the comparison of the checksums will be known whether a file is changed or not, by trying to apply it to prove results on microsoft office document file and pdf